Phase II Study of Everolimus and Octreotide LAR in Patients with Nonfunctioning Gastrointestinal Neuroendocrine Tumors: The GETNE1003_EVERLAR Study. (23rd May 2018) - Capdevila, Jaume; Teulé, Alexandre; Barriuso, Jorge; Castellano, Daniel; Lopez, Carlos; Manzano, Jose Luis; Alonso, Vicente; García‐Carbonero, Rocío; Dotor, Emma; Matos, Ignacio; Custodio, Ana; Casanovas, Oriol; et al.
Abstract: Background: Antitumor activity of the combination of somatostatin analogues (SSAs) and the mammalian target of rapamycin (mTOR) inhibitor everolimus in patients with neuroendocrine tumors (NETs) has been reported but not confirmed in prospective trials. Materials and Methods: This prospective, multicenter, single‐arm phase II EVERLAR study evaluated everolimus 10 mg/day and the SSA octreotide 30 mg every 28 days in patients with advanced nonfunctioning well‐differentiated gastrointestinal NETs (GI‐NETs) that progressed in the last 12 months (ClinicalTrials.gov NCT01567488). Prior treatment with SSAs and any systemic or locoregional therapy was allowed except for mTOR inhibitors. Patients continued treatment until disease progression or unacceptable adverse events (AEs). The primary endpoint was progression‐free survival (PFS) at 12 months; secondary endpoints included early biochemical response, objective response rate (ORR) by RECIST v1.0, overall survival (OS), AEs, activation of mTOR pathway (insulin‐like growth factor 1 receptor [IGF1R] and phosphoS6 [pS6] expression). Results: Forty‐three patients were included in the intent‐to‐treat analyses. After 12 months of treatment, 62.3% (95% confidence interval [CI] 48%–77%) of patients had not progressed or died. The 24‐month PFS rate was 43.6% (95% CI 29%–58%). The confirmed ORR was 2.3%, and stable disease was 58.1%. Median OS was not reached after 24 months of median follow‐up. Dose reductions and temporary interruptions due to AEs were required in 14 (33%) and 33 (77%) patients, respectively. The most frequent AEs were diarrhea, asthenia, mucositis, rash, and hyperglycemia. No correlation was observed between IGFR1 and pS6 expression and PFS/OS. Conclusion: The everolimus‐octreotide combination provided clinically relevant efficacy in nonfunctioning GI‐NETs, similar to the results of RADIANT‐2 in functioning setting. Implications for Practice: The EVERLAR study reports prospective data of somatostatin analogue in combination with everolimus in nonfunctioning gastrointestinal neuroendocrine tumors suggesting meaningful activity and favorable toxicity profile that supports drug combination in this setting. Abstract : The EVERLAR study was conducted to assess the anti‐tumor activity of the everolimus and the somatostatin analog octreotide combination in progressive nonfunctioning gastrointestinal neuroendocrine tumors and to understand the relationship between the activation of the translation of IGFR‐PI3K‐mTOR signal and response to treatment.